PENGABDIAN KEPADA MASYARAKAT BERBASIS KEAHLIAN OTOMOTIF MELALUI SERVIS GRATIS KENDARAAN BERMOTOR PADA EVENT SIKKA NAKER FEST - Romualdus Paulus Sogen; Desiderius Siga Meli Poa; Gusti F.X.Wara Wangge; Rikardus Dole (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2026)
This community service activity aims to apply automotive expertise through free vehicle servicing at the Sikka Naker Fest event in Sikka Regency, East Nusa Tenggara. This activity was motivated by the low public awareness of the importance of regular vehicle maintenance. The method used was descriptive qualitative, with data collection techniques through observation, short interviews, and activity documentation. The activity implementation included preparation, minor vehicle servicing, and activity evaluation. The results showed that most vehicles experienced minor technical problems, such as unusable oil and suboptimal brake and chain adjustments. The free servicing had a positive impact on improving vehicle performance and public understanding of vehicle maintenance. The community responded positively and felt helped by this activity. This automotive expertise-based community service activity was effective in improving driving safety and providing direct benefits to the community.